University Research Management: Trends in International Studies - Kurniadi, Romi; Sulistiyo, Urip; Yaldi, Destri; Ekasari, Novita (Anterior Jurnal, 2024)
This study seeks to reveal trends in higher education research management as a response to the importance of higher education’s contribution to bringing novelty to science through solid research management. The research method of systematic literature review through the PRISMA guideline approach was carried out to see the trends of various studies related to higher education research management. The results of the study show that the trend of higher education research management has begun to move from institutional grant management to project-based research management and expertise. The research data base system has entered the realm of substance that can be widely accessed as a form of contribution to science as well as efforts to downstream research results. Gender-sensitive research management is also a trend found in this study.